Phlegmasia cerulea dolens superimposed on disseminated intravascular coagulation in COVID-19.: Phlegmasia and disseminated intravascular coagulation in COVID-19. - Orso, Daniele; Mattuzzi, Lisa; Scapol, Sara; Delrio, Silvia; Vetrugno, Luigi; Bove, Tiziana (Acta Biomedica Atenei Parmensis, 2021)
COVID-19 infection has several cardiovascular implications, and coagulopathy is a common abnormality in these patients, often coupled with elevated plasma fibrinogen and D-dimer levels, contributing to adverse outcomes. Phlegmasia cerulea dolens (PCD) is a rare manifestation of deep vein thrombosis. It is life-threatening and can rapidly lead to venous gangrene of the extremity. Only a few cases of COVID-19 associated with PCD are reported in the literature, despite thromboembolism being the common paradigm between the two diseases. We present the case of a 64-year-old adult with acute severe COVID-19 pneumonia who developed PCD despite constantly elevated activated partial thromboplastin time and international normalized ratio.